SEMEN QUALITY OF WORKERS OCCUPATIONALLY EXPOSED TO BUSINESS, DRIVING AND COOKING. - DEREDDY NAGALINGA REDDY; KADIRI PULLANNA; GUNDALA HAROLD PHILIP (International Journal of Pharma and Bio Sciences, 2015)
Semen analysis of men occupationally exposed to business, driving and cooking from a cross section of population of Anantapurm district, Andhra Pradesh, India was done as it provides a useful profile of the function of the male reproductive health. Twenty four (24) men of each occupation, working in business, driving and involved in cooking were selected, of which twelve (12) belonged to age group of 21-30 and twelve in the age group of 31-40. Different semen parameters like volume, liquefaction, alkalinity, sperm count, motility and morphology were observed. Incidences of Hypospermia 51 in persons, Teratozoospermia 16, Oligozoospermia 58, Oligoasthenozoospermia 21, and Oligoasthenoteratozoopermia 12 were observed in men of all three occupations indicating that these occupations are potential hazards for men as their reproductive health was affected in men of these occupations